Hiperinformação e desinformação na perspectiva da Arquivologia pós-custodial - ARAÚJO, Maria Luiza Ferreira de (2023)
The present work presents a bibliographic review, based on Capes Periodicals, with the objective of analyzing the concepts of Hyperinformation and Misinformation, in the area of Archival Science. It is noteworthy that we start from the assumptions of the post-custodial paradigm and the notion of Information Competence. The terms mentioned above were associated with another search string: Archival Science. With these terms, eight articles were found: two in English and the third with private access. Thus, we analyzed five works and concluded that despite the low scientific production, the field of archival science has been concerned with contemporary issues about its guiding object of the post-custodial paradigm which is information, in the case of this present work, the negative effect of information.